Theoretical analysis of projectile-target interface defeat and transition to penetration by long rods due to oblique impacts of ceramic targets. (August 2017) - Li, J.C.; Chen, X.W.
Highlights: Corresponding formulae considering the influence of obliquity angle are deduced. Critical impact velocity range within which transition occurs is further discussed. Critical transition time is analysed and its theoretical formula is deduced out. Comparison between the normal and oblique impacts is conducted in detail. Abstract: Integrated with related investigations, the present manuscript conducts systematical theoretical analysis on the interface defeat (the phenomenon where an impacting eroding projectile flows radially outward along the surface of target without any significant penetration) of long rods under the oblique impacts onto ceramic targets, and related comparison with the normal impact is also carried out. By taking the influence of obliquity angle into account, the corresponding formulae for the velocity decay and the mass erosion of long rods with time are deduced out, and the kinetic energy loss is further discussed. Moreover, the transition from interface defeat to penetration is analyzed in detail. The variation characteristic of critical impact velocity range with the increase of obliquity angle is discussed, and the critical transition time is deduced considering the damage and failure characteristics of the ceramic target. Furthermore, the corresponding theoretical expressions are formulated. Finally, some suggestions for optimizing the design of ceramic target are given based on related analysis.